Elements That Contribute to Customer Satisfaction - Danibrata, Aulia; Sutrisno, Nuno; Kusuma , Gabriel Adinda Vidya (Journal of Business Social and Technology, 2024)
The telecommunications business situation in Indonesia currently plays an essential role in the national economy. The rapid advancement of technology in Indonesia is increasing, which causes a high need for adequate telecommunication facilities. This telecommunications need aims to support ease in disseminating information and a tool for communicating from one place to another. The essence of this study is to determine the effect of brand trust, brand equity, and social media marketing on brand loyalty among Telkomsel users. The method used is descriptive quantitative and data collection using primary data in the form of a questionnaire. Respondents in this study were individuals who bought the products at least three times in a particular time. The respondents who were determined by the study were 203 sample people. The analysis technique used is Structural Equation Modeling. The results of this study indicate that brand trust and equity affect brand loyalty, while social media marketing has no effect on brand loyalty. As well as with the outbreak of the COVID-19 virus, the spread is only through online surveys, which are less efficient because they need to interact directly with respondents. This study successfully obtained 214 respondents but only 203 valid or usable data.